The effects of psychological contract fulfillment on perceived fairness of performance appraisal among working Generation Y / Aqilah Mohamed - Mohamed, Aqilah (Faculty of Business and Management, 2019)
Previous literatures have paid substantial attention to the importance of perceived fairness of performance appraisal system in high-performing organization. However, one of the major commotion faced by Human Resource Management (HRM) is to establish both an effective and a fair performance appraisal system. Little is known about the key organizational and psychological factors that affect perceived fairness of performance appraisal, especially on Malaysia Y-Generation. Yet, most studies have focused on the structural factors rather than the psychological standpoints in regards to employees’ perceived fairness of performance appraisal system. Drawing upon the effects of psychological contract fulfillment which is the expectations between an employee and the employer, this study examines whether psychological contract fulfillment are associated with perceived fairness of performance appraisal among working Generation Y. Using instruments by previous researcher, 180 questionnaires have been distributed to the working Generation Y and 123 have been duly filled for this study. The collected data were codified and analyzed by using Statistical Package for the Social Sciences (SPSS). From the findings, the study inferred that psychological contract fulfillment have a positive impact working Generation Y’s perceived fairness of performance appraisal.